PROCESSING WASTE COOKING OIL INTO CANDLES: ENVIRONMENTAL EDUCATION AND COMMUNITY ECONOMIC IMPROVEMENT: PENGOLAHAN LIMBAH MINYAK JELANTAH MENJADI LILIN: EDUKASI LINGKUNGAN DAN PENINGKATAN EKONOMI MASYARAKAT - Arofah Minasari; Erina Ikawati; Vercelli Gipsy Angelica Larasati; AK Paksi Kencana (Faculty of Vocational Studies, Universitas Airlangga, 2026)
Background: Used cooking oil (UCO) is a domestic waste that increases in volume along with high consumption of cooking oil in Indonesia and has the potential to harm human health and the environment if not managed properly. Objective: Management of cooking oil waste into aromatherapy candles as an environmental education and a community economic empowerment was designed based on the circular economy. Method: An approach with participatory action research (PAR) paradigm, which used stages of preparation, outreach, training, product processing, then evaluation and mentoring to reach active community participation in the form of creative economic development. Results: The technical knowledge of the participants increased by 26 percentage points, and their confidence increased by 34 percentage points. Activated charcoal was effective for the reduction of rancid odors, and the essential oils improved the functional and economic value of the product. The candles produced showed steady burning behaviours and an acceptable quality of the end product for home production. Conclusion: The processing of WCO into aromatherapy candles would be an effective way to reduce environmental pollution in tandem with enhancing community empowerment and bolstering the emergence of micro-scale enterprises around waste utilizations.